Variations in the wind‐energy regime of the Taklimakan Desert, central Asia, over the last 700 years as inferred from nebkha sedimentology and chronology. (15th January 2014) - Wang, Xunming; Lang, Lili; Hua, Ting; Zhang, Caixia; Li, Hui
<x xml:space="preserve">Abstract</x> Changes in the wind‐energy environment between AD 1359 and 2010 in the Taklimakan Desert (central Asia) are recorded by the evolution of Chinese tamarisk (Tamarix taklamakanensis) nebkhas. The carbonate component and sedimentological properties of the nebkha excavated during the study, together with AMS 14C dating control, indicate that significant regional environmental changes have occurred in the central Taklimakan Desert during the last 700 years. The nebkha data presented show that in the periods of AD c. 1480–1560, c. 1640–1690, c. 1760–1820, c. 1860–1930 and c. 1970–1980 the Taklimakan Desert was a relatively high wind‐energy environment. Although changes in the wind‐energy regime in the desert were mainly in phase with fluctuations of the Siberian High, the wind systems and the variations in wind energy exhibit slight differences when compared with the Tarim Basin. Nebkhas that develop in this region originate from the surfaces of mobile dunes or sand sheets, which differs from the origins of nebkhas found in other arid regions of China.